2022
DOI: 10.3390/agronomy12051198
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Tolerance Options for Weed Control in Lanza® Tedera

Abstract: Tedera is a drought-tolerant perennial forage legume introduced in Australia in 2006. In October 2018, T15-1218 Lanza®, the world’s first tedera variety, was released by the Department of Primary Industries and Regional Development and Meat & Livestock Australia for commercial use. A key agronomic practise for the successful establishment and adoption of tedera is to have a robust herbicide package to control a range of grass and broadleaf weeds well tolerated by tedera. A total of 9 pre-emergent and 44 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The overall main alternatives could be (i) crop rotations to reduce weed burden, (ii) leaving the fields fallow during the season before sowing to avoid seed production of forbs and grasses, (iii) strategic grazing management, and (iv) the use of herbicides. Recently, Real et al [27] have provided options for a herbicide package for weed control in LANZA ® . They found that propyzamide and carbetamide as pre-or post-emergent applications and butroxydim, clethodim, and haloxyfop for post-emergent applications can be recommended to control grasses such as annual ryegrass (Lolium rigidum) [27].…”
Section: Effect Of Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall main alternatives could be (i) crop rotations to reduce weed burden, (ii) leaving the fields fallow during the season before sowing to avoid seed production of forbs and grasses, (iii) strategic grazing management, and (iv) the use of herbicides. Recently, Real et al [27] have provided options for a herbicide package for weed control in LANZA ® . They found that propyzamide and carbetamide as pre-or post-emergent applications and butroxydim, clethodim, and haloxyfop for post-emergent applications can be recommended to control grasses such as annual ryegrass (Lolium rigidum) [27].…”
Section: Effect Of Competitionmentioning
confidence: 99%
“…Recently, Real [25] demonstrated that this species could be established using machinery commonly used for cereal establishment and provided information about fertilization requirements [26] and herbicide tolerance [27].…”
Section: Introductionmentioning
confidence: 99%
“…With pyroxasulfone recently coming off-patent and its inclusion in new herbicide formulations, its use in cropping, and therefore the risk of resistance evolution in agricultural weeds, is expected to increase. The aim of the current study was to assess the ability of several L.…”
Section: Introductionmentioning
confidence: 99%
“…In both wheat and L. rigidum, the belowground tissues had significantly higher GST pyrox activity than the green tissues, and a proteomic study indicated that an orthologue of Brachypodium distachyon GSTF13 may be responsible for the GST pyrox activity in the seeds and radicles of L. rigidum. 17 With pyroxasulfone recently coming off-patent and its inclusion in new herbicide formulations, 18 its use in cropping, and therefore the risk of resistance evolution in agricultural weeds, is expected to increase. The aim of the current study was to assess the ability of several L. rigidum populations with suspected field-evolved pyroxasulfone resistance to conjugate the herbicide to GSH and investigate whether GSTF13-like isoforms are involved in conjugation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The animal production research concluded that: (a) grazing tedera did not cause any ill-effect to the grazing animals even when grazed as a sole diet or in mixtures at different times of the year [9][10][11] and (b) tedera proved to be a valuable summer and autumn feed for sheep in Mediterranean-like climates [5]. The agronomy package for a newly domesticated species needs to cover all aspects of crop production, such as establishment techniques [12], herbicide tolerance [13], harvesting technologies under local conditions and an understanding of the P, K and S requirements for optimum production.…”
Section: Introductionmentioning
confidence: 99%